2001
DOI: 10.1038/sj.bjp.0704436
|View full text |Cite
|
Sign up to set email alerts
|

Interactive contribution of NK1 and kinin receptors to the acute inflammatory oedema observed in response to noxious heat stimulation: studies in NK1 receptor knockout mice

Abstract: Scald injury in Sv129+C57BL/6 mice induced a temperature and time dependent oedema formation as calculated by the extravascular accumulation of [125I]‐albumin. Oedema formation was suppressed in NK1 knockout mice compared to wildtypes at 10 (P<0.01) and 30 min (P<0.001). However, at 60 min a similar degree of extravasation was observed in the two groups. Kinin B1 (des‐Arg10 Hoe 140; 1 μmol kg−1) and B2 (Hoe 140; 100 nmol kg−1) antagonists caused an inhibition of oedema in wildtype mice at 10 and 30 min (P<0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In contrast to studies of acute nociception, numerous studies have shown that B 1 antagonists are antihyperalgesic in animal models of persistent inflammation (Perkins et al, 1993;Bélichard et al, 2000;Rawlingson et al, 2001), as well as in persistent visceral pain (Jaggar et al, 1998). Des-Arg 9 -[Leu 8 ]-BK, a B 1 receptor antagonist (Marceau and Regoli, 2004) inhibits carrageenan-induced hyperalgesia and formalin-induced paw flick (Rupniak et al, 1997), as well as edema and hyperalgesia associated with burn injuries (Perkins et al, 1993;Rawlingson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies of acute nociception, numerous studies have shown that B 1 antagonists are antihyperalgesic in animal models of persistent inflammation (Perkins et al, 1993;Bélichard et al, 2000;Rawlingson et al, 2001), as well as in persistent visceral pain (Jaggar et al, 1998). Des-Arg 9 -[Leu 8 ]-BK, a B 1 receptor antagonist (Marceau and Regoli, 2004) inhibits carrageenan-induced hyperalgesia and formalin-induced paw flick (Rupniak et al, 1997), as well as edema and hyperalgesia associated with burn injuries (Perkins et al, 1993;Rawlingson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Des-Arg 9 -[Leu 8 ]-BK, a B 1 receptor antagonist (Marceau and Regoli, 2004) inhibits carrageenan-induced hyperalgesia and formalin-induced paw flick (Rupniak et al, 1997), as well as edema and hyperalgesia associated with burn injuries (Perkins et al, 1993;Rawlingson et al, 2001). LF22-0542 also showed activity in models of inflammatory pain including significant antihyperalgesic actions in the second phase of the formalin response in both mice and rats and in both acute (carrageenan) and persistent (CFA) inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of Myeloperoxidase Activity in Mouse Ear-Myeloperoxidase (MPO), located in the azurophilic granules of neutrophils, has been used as an enzyme marker of neutrophil infiltration into inflamed tissues (45). MPO activity in the mouse ear was estimated as described in Ref.…”
Section: Estimation Of the Amounts Of Individual Molecular Species Ofmentioning
confidence: 99%
“…The therapeutic interest of B 1 receptor blockage is supported further by the pharmacological properties of B 1 peptide antagonists. Edema and hyperalgesia associated to burn injuries are attenuated by desArg 9 ,Leu 8 -BK Rawlingson et al, 2001). The peptide inhibitor R-954 was shown to reduce eosinophil and neutrophil infiltration and airway hyperreactivity induced by lung inflammation (Gama Landgraf et al, 2003).…”
mentioning
confidence: 99%